TOPOLOGY OPTIMIZATION OF MORPHING WING TRAILING EDGE BASED ON MULTI-POINTS DRIVING COMPLIANT MECHANISM - KOU Xin; GE WenJie (Jixie qiangdu)
The wing is designed by specific flight conditions,and its aerodynamic efficiency under various conditions needs to be optimized.This paper studies the trailing edge of the morphing wing to make it meet the aerodynamic optimal deformation range under the premise of continuous smooth deformation.By using the method of topology optimization with variable density method,the minimum square error between the actual displacement of the airfoil and the target displacement is taken as the optimization objective function,and the position of the trailing edge multi-point driving load is optimized by genetic algorithm to establish the compliant trailing edge comprehensive optimization model.Using the moving asymptotic method to solve.Finally,the result was simulated by ANSYS,the effectiveness of trailing edge deformation is discussed and verified.